Hepatocyte growth factor/scatter factor and its interaction with heparan sulphate and dermatan sulphate. (1st April 2003) - Catlow, K.; Deakin, J.A.; Delehedde, M.; Fernig, D.G.; Gallagher, J.T.; Pavão, M.S.G.; Lyon, M.
Abstract : Hepatocyte growth factor (HGF)/scatter factor (SF) is a unique growth factor, in that it binds both heparan sulphate (HS) and dermatan sulphate (DS). The sequences in HS and DS that specifically interact with and modulate HGF/SF activity have not yet been fully identified. Ascidian DS, which uniquely possesses O-sulphation at C-6 (and not C-4) of its N -acetylgalactosamine unit, was analysed for HGF/SF-binding activity in the biosensor. The kinetic analysis revealed a strong, biologically relevant interaction with an equilibrium dissociation constant ( K d ) of approx. 1 nM. An Erk activation assay also demonstrated stimulation of the MAP kinase pathway downstream of the Met receptor following addition of both HGF/SF and ascidian DS to the glycosaminoglycan-deficient CHO-745 mutant cell line. Furthermore, the activation of Met and the MAP kinase pathway by HGF/SF and ascidian DS leads to a cellular response in the form of migration.